Presenting the quality of life model related to the health of patients with type 2 diabetes based on disease perception and demographic characteristics with the mediating role of self-care behaviors - Pourrostami, Ahmad; Zarbakhsh Bahri, Mohammadreza; Bahrami, Sobhan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Type 2 diabetes, which is the most common type of this disease, is caused by the inefficiency of the body regarding the proper use of insulin, and this disease can affect the quality of life of affected patients due to its chronic nature. The present study was conducted with the aim of providing a health-related quality of life model for type 2 diabetes patients based on disease perception and demographic characteristics with the mediating role of self-care behaviors. Methods: The method of this study was correlation type. The statistical population of this study was all patients with type 2 diabetes who had visited the hospitals of Tonkabon and Ramsar cities within a six-month interval. 350 patients were selected by available sampling method. The data were obtained using the health-related quality of life questionnaire (Baroghs et al., 2004), the illness perception questionnaire (Weinman et al., 1996), the self-care behavior questionnaire (Tobert et al., 2000) and the demographic characteristics questionnaire. Came. Data analysis was done by structural equation method and using SmartPLS and SPSS software. Results: The results showed that there is a negative and significant relationship between the perception of the disease and the quality of life related to the patients' health (P